Contrast-Induced Nephropathy: Update on the Use of Crystalloids and Pharmacological Measures - D. Patschan; I. Buschmann; O. Ritter (International Journal of Nephrology)
Contrast-induced nephropathy (CIN) is a frequent and severe complication in subjects receiving iodinated contrast media for diagnostic or therapeutic purposes. Several preventive strategies were evaluated in the past. Recent clinical studies and meta-analyses delivered some new aspects on preventive measures used in the past and present. We will discuss all pharmacological and nonpharmacological procedures. Finally, we will suggest individualized recommendations for CIN prevention.